Illegal psychoactive substance consumption amongst older schoolchildren in the city of tunja, colombia (2012)
Objectives Assessing lifetime prevalence of illegal substance use and accessibility to such substances. Determining risk factors and the protective factors linked to them. Methods This was a cross-sectional study using descriptive and bivariate analysis. A survey was applied to 1,515 students from 8th to 11th grades in the city’s schools, ages ranging from 12 to 18.Results An increase in lifetime prevalence and lower age for consumption onset were found. The main risk factors were determined to be academic environment and attitudes towards school authorities, linked to recreational and sports groups without control by elders, gang membership and engaging in risky and dangerous activities. Conclusions The results showed the need for a critical review of current promotion and prevention strategies aimed at controlling the use of psychoactive substances amongst children and adolescents, according to the current reality of trafficking and domestic consumption in Colombia.